2014
DOI: 10.3109/07434618.2013.875590
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Mosaic of Supports Required for Including People with Severe Intellectual or Developmental Disabilities in their Communities

Abstract: The goal of this Forum article is to examine the progress that has been made over the past 20 years in providing opportunities for community living, inclusive schooling, and integrated employment to people with severe intellectual or developmental disabilities who rely on Augmentative and Alternative Communication (AAC). Recent research and statistical data from the United States and elsewhere are used to describe both the gains that have been made and the challenges that still remain. Directions for future ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 40 publications
0
30
0
1
Order By: Relevance
“…In a review of 15 DA studies that used Pearson’s correlation coefficients to measure predictive validity of DA, Caffrey, Fuchs, and Fuchs (2008) found that in general, DA was predictive of subsequent performance, particularly when applied to students with disabilities rather than at-risk or typically achieving students. In other words, children with disabilities were the most likely to show rapid learning gains when provided with appropriate supports – which may be evidence that these children frequently are not provided with appropriate supports (Mirenda, 2014). The results of Ben, Carmen, and Darryl provide further support for these findings and contribute to the growing body of evidence that supports the predictive validity of DA.…”
Section: Discussionmentioning
confidence: 99%
“…In a review of 15 DA studies that used Pearson’s correlation coefficients to measure predictive validity of DA, Caffrey, Fuchs, and Fuchs (2008) found that in general, DA was predictive of subsequent performance, particularly when applied to students with disabilities rather than at-risk or typically achieving students. In other words, children with disabilities were the most likely to show rapid learning gains when provided with appropriate supports – which may be evidence that these children frequently are not provided with appropriate supports (Mirenda, 2014). The results of Ben, Carmen, and Darryl provide further support for these findings and contribute to the growing body of evidence that supports the predictive validity of DA.…”
Section: Discussionmentioning
confidence: 99%
“…The expectations for the participation of individuals with complex communication needs within society also have changed dramatically. Whereas 25 years ago many individuals who required AAC were living in large residential institutions with limited educational and vocational opportunities, now individuals with complex communication needs live, go to school, work, and participate within their communities (Mirenda, 2014). These changes have resulted in increased communication demands that must be addressed through AAC intervention, in order to ensure that individuals with complex communication needs develop the necessary knowledge, judgment, and skills to ensure communicative competence.…”
Section: Discussionmentioning
confidence: 99%
“…The challenge is to develop effective evidence-based, culturally-competent AAC interventions to support these individuals in the realization of communicative competence, so that they are able to express their needs and wants, develop social closeness, exchange information, and participate in social etiquette routines as desired at home, at school, at work and/or in the community. Twenty-fi ve years ago, the fi eld was focused on demonstrating what was possible with access to appropriate AAC interventions (Mirenda, 2014). Now that the possible has been established, the challenge will be to ensure that it becomes the probable and that every individual with complex communication needs has access to effective evidence-based AAC intervention to maximize participation and communication (Beukelman et al, 2007;Rispoli, Franco, van der Meer, Lang, & Camargo, 2010).…”
Section: Future Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Stancliffe et al (2010) reported that 91% of adults with severe intellectual and developmental disabilities do not have access to AAC and have no means to participate within activities of daily living; 77% of individuals with multiple disabilities do not engage in any type of community activity, largely due to communication diffi culties (Wagner et al, 2005). Given the increase in knowledge over the past 30 years, why do persons with complex communication needs (and their communication partners) continue to struggle to achieve successful interaction and the pursuit of valued outcomes (Johnson, Douglas, Bigby, & Iacono, 2009;Mirenda, 2014)? Essentially the challenge is two-fold: There is a need to re-think both AAC intervention and research in order to transform these outcomes.…”
Section: Introductionmentioning
confidence: 99%